2015
DOI: 10.1007/s13277-015-4317-y
|View full text |Cite
|
Sign up to set email alerts
|

Hotspot TERT promoter mutations are rare events in testicular germ cell tumors

Abstract: The abnormal activation of telomerase, codified by the telomerase reverse transcriptase (TERT) gene, is related to one of cancer hallmarks. Hotspot somatic mutations in the promoter region of TERT, specifically the c.-124:C>T and c.-146:C>T, were recently identified in a range of human cancers and have been associated with a more aggressive behavior. Testicular germ cell tumors frequently exhibit a good prognosis; however, the development of refractory disease is still a clinical challenge. In this study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In our cohort of TGCT patients, we recently reported that well‐known hallmarks of cancer, as microsatellite instability (MSI), V600E BRAF , and TERT promoter mutations, are not present (Carcano et al ., ,b). Recently, Bagrodia et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of TGCT patients, we recently reported that well‐known hallmarks of cancer, as microsatellite instability (MSI), V600E BRAF , and TERT promoter mutations, are not present (Carcano et al ., ,b). Recently, Bagrodia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent mutations in the death-associated protein (DAXX) and the alphathalassemia X-linked protein (ATRX) have been correlated with ALT occurrence and potentially contribute to ALT maintenance 33,34 . Of note, there is evidence that telomerase activity supresses ALT, although the suppressive mechanism is yet to be identified [34][35][36][37][38][39][40][41][42][43][44][45][46][47] . In a comprehensive analysis of 6,110 human tumour specimens from various cancer types, ALT was observed in only ~4% of samples 48 .…”
Section: Takedownmentioning
confidence: 99%
“…Please provide further evidence to back up your statement. ] By contrast, the absence of TERT promoter mutations in cancers arising from highly proliferative tissues with a stem cell compartment 38,132 . [Au:Please add examples and reference.]…”
Section: Ectopic Expression Of the C-mentioning
confidence: 99%
“…The most noticeable conclusion from these findings is that, irrespective of the reactivation mechanism, the data support the idea that at least a subset of tumors originate from an initially telomerase negative cell. Remarkably, hTERT promoter mutations are frequently detected in cancers with low self-renewal rates [55,56,57,58,59,60,61,62] whereas they are extremely rare in tumors originating from highly proliferating tissues [63,64,65]. We suggest that hTERT promoter mutations may account for both reactivation concepts 1 and 2.…”
Section: Telomerase Reactivation Versus Telomerase Positive Stem Cmentioning
confidence: 84%
“…On the other hand, other tumor entities have a low frequency or no hTERT promoter mutations which are described up to the recent date, including testicular germ cell tumors, colorectal adenocarcinoma, pancreatic cancer, papillary thyroid cancers, and most types of leukemia [63,64,65] despite high telomerase activity in these tumors [66,67,68]. These observations indicate that other mechanisms, e.g., loss of negative regulatory factors or chromatin remodeling may be responsible for telomerase reactivation in the tumor types (e.g., loss of suppression: see above).…”
Section: Regulatory Mechanisms Involved In Tert Gene Regulation Inmentioning
confidence: 99%